Generalities on the resistant personality as quality of the endurance athlete (Revista científica Olimpia, 2015)
The hardiness personality is an individual characteristic that allow us to be ready against stressors stimulation of the life, and become it in growing opportunity (kobasa, 1979, maddi, 2006). There are three components: compromise, control and challenge that could protect the athletes against unespecting situations at the endurance. The article make supporting in nowadays matters according to the principal characteristics which have the endurance athletes and  specially to the characteristic about that kind of personality This matter is taken to account in every time by all trainmen inside of the psychological training of theirs athletes and in the endurances it have an special significance.
Keywords: hardiness; endurance; personality; stress